Bystander Assistance for Trauma Victims in Low- and Middle-Income Countries: A Systematic Review of Prevalence and Training Interventions. (4th May 2019) - Balhara, Kamna S.; Bustamante, Nirma D.; Selvam, Anand; Winders, W. Tyler; Coker, Amin; Trehan, Indi; Becker, Torben K.; Levine, Adam C.
Abstract: Objective: Lack of organized prehospital care may contribute to the disproportionate burden of trauma-related deaths in low- and middle-income countries (LMICs). The World Health Organization (WHO) recommends bystander training in basic principles of first aid and victim transport; however, prevalence of bystander or layperson assistance to trauma victims in LMICs has not been well-described, and organized reviews of existing evidence for bystander training are lacking. This systematic review aims to 1) describe the prevalence of bystander or layperson aid or transport for trauma victims in the prehospital setting in LMICs and 2) ascertain impacts of bystander training interventions in these settings. Methods: A systematic search of OVID Medline, Cochrane Library, and relevant gray literature was conducted. We included 1) all studies detailing prevalence of bystander-administered aid or transport for trauma victims in LMICs and 2) all randomized controlled trials and observational studies evaluating bystander training interventions. We extracted study characteristics, interventions, and outcomes data. Study quality was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Results: Sixty-two studies detailed prevalence of bystander transport and aid. Family members, police, and bus or taxi drivers commonly transported patients; a majority of patients, up to >94%, received aid from bystanders. Twenty-four studies examined impacts of training interventions. Only one study looked at transport interventions; the remainder addressed first aid training. Interventions varied in content, duration, and target learners. Evidence was generally of low quality, but all studies demonstrated improvements in layperson knowledge and skills. Five studies reported a mortality reduction. Conclusions: Heterogeneity in data reporting and outcomes limited formal meta-analysis. However, this review shows high rates of bystander involvement in prehospital trauma care and transport in LMICs and highlights the need for bystander training. Bystander training in these settings is feasible and may have an important impact on meaningful outcomes such as mortality. Categories of involved bystanders varied by region and training interventions should be targeted at relevant groups. "Train the trainer" models appear promising in securing community engagement and maximizing participation. Further research is needed to examine the value of bystander transport networks in trauma.